2014
DOI: 10.1371/journal.pone.0094193
|View full text |Cite
|
Sign up to set email alerts
|

Assumed White Blood Cell Count of 8,000 Cells/μL Overestimates Malaria Parasite Density in the Brazilian Amazon

Abstract: Quantification of parasite density is an important component in the diagnosis of malaria infection. The accuracy of this estimation varies according to the method used. The aim of this study was to assess the agreement between the parasite density values obtained with the assumed value of 8,000 cells/μL and the automated WBC count. Moreover, the same comparative analysis was carried out for other assumed values of WBCs. The study was carried out in Brazil with 403 malaria patients who were infected in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 14 publications
5
21
0
Order By: Relevance
“…Nonetheless, this notion has been repeatedly observed in similar studies conducted in other malaria-endemic regions (Table 4). Of particular notice is that despite regional difference, the assumed WBC count of 5,500 cells/µl from this study coincided well with the proposed WBC count in a region of the Brazilian Amazon, where the majority (92.6%) of the study subjects was adults (Alves-Junior et al, 2014). An assumed WBC count of 5,000 cells/µl for patients five years and older matched well with a recent finding in south-western India, where all patients were adults and infected with P. vivax only (Rishikesh et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Nonetheless, this notion has been repeatedly observed in similar studies conducted in other malaria-endemic regions (Table 4). Of particular notice is that despite regional difference, the assumed WBC count of 5,500 cells/µl from this study coincided well with the proposed WBC count in a region of the Brazilian Amazon, where the majority (92.6%) of the study subjects was adults (Alves-Junior et al, 2014). An assumed WBC count of 5,000 cells/µl for patients five years and older matched well with a recent finding in south-western India, where all patients were adults and infected with P. vivax only (Rishikesh et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…The World Health Organization (WHO) recommended the use of an assumed WBC value of 8,000/µl (WHO, 2010), which was based on a study with a Nigerian population with a large proportion of children younger than five years (Dowling and Shute, 1966). Yet, recent studies found that estimating malaria parasite densities using this WBC value yielded results that were inconsistent with the actual observed malaria parasite density of patients in some areas (Alves-Junior et al, 2014; Jeremiah and Uko, 2007; McKenzie et al, 2005; Rishikesh et al, 2015). Furthermore, whereas most studies conducted so far focused on P. falciparum patients, studies conducted in areas co-endemic for P. vivax and P. falciparum revealed considerable differences in WBC counts between patients infected with these two parasite species (Alves-Junior et al, 2014; McKenzie et al, 2005).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…A similar recommendation was recently made for malaria patients in the Brazilian Amazon, where an assumed WBC count of 5,500/μL (instead of 8,000/μL) was shown to more accurately estimate parasite density. 21 Second, it may be difficult to establish a single reference interval for hematological indices in healthy African children. For example, in children aged 6-12 years, the median Ht that we observed in Mali (36.7-40.1%) was higher or similar to that reported in Uganda (34.4%) 16 or Tanzania (38.4%), 17 Finally, our study has several strengths and limitations.…”
Section: Discussionmentioning
confidence: 99%